(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Burglary is a serious crime that can have a significant impact on individuals, families, and communities. Burglaries can result in the loss of valuable possessions damage to property, and can leave victims feeling violated and unsafe in their own homes. Despite efforts to prevent burglaries through various policies and measures, the number of burglaries continues to be a concern in many areas around the world. Therefore, it is important to conduct research that focuses on developing effective strategies for preventing burglaries and mitigating their impact on victiMs. This research paper aims to provide an overview of current policies and guidelines for burglary prevention and to propose recommendations for policy enhancement in order to create safer communities for residents. By examining the effectiveness of existing policies and developing new recommendations, this research paper seeks to contribute to the ongoing efforts to reduce the incidence and impact of burglaries. Many residents took part in our study, and they were classified into two groups: victims and barangay authorities. They expressed major difficulties in appraising burglary victims, owing mostly to a lack of protection in their houses and the psychological anguish it causes a victim. Local governments adopt preventive measures such as assigning private security to patrol areas where there is a high rate of theft. The findings highlight the importance of every resident’s protection and safety so that no one else becomes a victim of stealing. Following preventive steps will help to avoid these types of accidents. Local government initiatives are among the most significant; nevertheless, strengthening security and safeguarding the safety of all residents is even more critical.